High-performance novel asymmetric MXene@CNT//N-doped CNT flexible hybrid device with large working voltage for energy storage. (July 2023) - Dangbegnon, Julien; Garino, Nadia; Angelozzi, Matteo; Laurenti, Marco; Seller, Francesco; Serrapede, Mara; Zaccagnini, Pietro; Moras, Paolo; Cocuzza, Matteo; Ouisse, Thierry; Pazniak, Hanna; Gonzalez-Julian, Jesus; et al.
Abstract: We developed a novel fiber-shaped supercapacitor based on a hybrid MXene@CNT//N-doped CNT device. In particular, for the first time, electrophoretically deposited Ti3 C2 Tx MXenes on carbon nanotube yarns and microwave-assisted nitrogen-doped carbon nanotube yarns are proposed as negative and positive electrodes, respectively. Short-circuit encountered during cell assembly was prevented entirely by coating a reproducible polyvinylidene difluoride (PVDF) membrane directly on the electrodes. Based on the developed electrodes, the assembled cell exhibited a large operating voltage window of up to 2.0 V in a diluted 0.5 M H2 SO4 liquid electrolyte. The device displayed excellent stability over 5000 cycles with a Coulombic efficiency of nearly 100 %. The device withstood a floating test for 70 h with approximately 100 % capacity retention and exhibited excellent resistance to mechanical stress. Areal energy density as high as 298.5 μWh cm −2 was recorded for a power density value of 855.5 μW.cm −2 at an areal current value of 0.5 mA cm −2 . At a high current density of 10 mA cm −2, the energy density remained high at 99.0 μWh cm −2 for a corresponding power density of 8.11 mW cm −2 . The reported values rank among the highest obtained for carbon nanotubes-based wired-shaped supercapacitors and show the potential of this flexible wired-shaped hybrid energy storage unit as a wearable device. Graphical abstract: Unlabelled Image Highlights: Asymmetric MXene@CNT//N-doped CNT flexible hybrid device works within a large potential of 2.0 V in an aqueous electrolyte. Electrophoretic synthesis of MXene@CNT was demonstrated for the first time. The use of PVDF membrane improves the electrochemical performance of the full cell upon mechanical stress. The device exhibits high areal energy density and excellent stability upon the aging test